2010
DOI: 10.1007/s00540-010-0880-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the timing principle with high-dose rocuronium during rapid sequence induction with lidocaine, remifentanil and propofol

Abstract: Application of the timing principle with 1 mg kg(-1) rocuronium is beneficial for rapid tracheal intubation. Co-administered lidocaine, remifentanil and propofol can definitely suppress cardiovascular responses during laryngoscopy and intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…Hence, it is not suitable in situations like neuromuscular disorders, burns, acute head injury, intracranial bleed,[4] open eye injury, spinal cord injury,[5] cerebrovascular accidents and renal diseases. The above side-effects and contraindications of succinylcholine had prompted the use of non-depolarizing muscle relaxants using various techniques for rapid sequence intubation, such as (1) timing principles,[6] (2) combination of relaxant,[7] (3) high dose of non-depolarizing muscle relaxants,[8] (4) inhalational agents to augment the effect of non-depolarizing muscle relaxants,[9] (5) use of intravenous anaesthetic agents with non-depolarizing muscle relaxants to augment neuromuscular blockade[10] and (6) priming principle.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is not suitable in situations like neuromuscular disorders, burns, acute head injury, intracranial bleed,[4] open eye injury, spinal cord injury,[5] cerebrovascular accidents and renal diseases. The above side-effects and contraindications of succinylcholine had prompted the use of non-depolarizing muscle relaxants using various techniques for rapid sequence intubation, such as (1) timing principles,[6] (2) combination of relaxant,[7] (3) high dose of non-depolarizing muscle relaxants,[8] (4) inhalational agents to augment the effect of non-depolarizing muscle relaxants,[9] (5) use of intravenous anaesthetic agents with non-depolarizing muscle relaxants to augment neuromuscular blockade[10] and (6) priming principle.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, establishing a fast and profound neuromuscular block is required for rapid sequence intubation. Although priming [17] and timing principles [18] using rapid-onset rocuronium have been reported to be effective for rapid sequence intubation, suxamethonium seems to be clinically preferred rather than rocuronium as a neuromuscular blocking agent for patients with specific risks of pulmonary aspiration. In fact, a survey of variation of rapid sequence induction techniques in Wales reported that suxamethonium was currently used for 97% of cesarean sections, 94% of bowel obstructions, and 85% of appendectomies; in contrast, rocuronium was used only in 2-12% of patients [2].…”
Section: Discussionmentioning
confidence: 95%
“…Rocuronium has been shown to be as effective as succinylcholine in facilitating laryngoscopy during RSII [5,6]. Administration of rocuronium (1 mg/kg) immediately prior to administration propofol facilitates good to excellent intubating conditions within 60 s of dosing in non trauma patients, which is comparable to succinylcholine [4,7]. There is limited data regarding the use of vecuronium for RSII, and this agent is not generally recommended due to a longer onset time (80-140 s), even when larger doses are used (0.3 mg/kg) [8][9][10].…”
Section: Induction Agentsmentioning
confidence: 99%